PELATIHAN PENGUKURAN JALAN REL MENGGUNAKAN MESSREG CDM DI BALAI PERAWATAN PERKERETAAPIAN - Prihatanto, Rusman; Wiarco, Yuwono; Nurhadi, Muhammad; Aghastya, Adya; Adi, Wahyu Tamtomo; Astuti, Septiana Widi; Malaiholo, David; Kurniawan, Muhammad Adib (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
Community service activities are carried out by providing training to Railway Maintenance Center employees in using the Messreg CDM which is used to measure the width of railroad tracks and obtain other parameters, such as elevation, widening, twist, back-to-back distance and several other parameters. Training activities are carried out by providing class material regarding the components/parts of the Messreg CDM measuring instrument, and how to download measurement results and analyze and compare them with applicable standards. Next is the practice of measuring in the field, which is carried out on train tracks in the Railway Maintenance Center workshop. The practice here is carried out so that participants understand more about the Messreg CDM measuring instrument because they learn how to assemble it, set up a laptop, carry out measurements and troubleshoot problems that might occur. After the training, the Railway Maintenance Center employees who took part in the training showed increased ability, both in operating and analyzing data obtained from measurement results. This will of course support the implementation of the duties and functions of the Railway Maintenance Center